Near-bottom temperature data obtained from Current and Pressure-recording Inverted Echo Sounders (CPIES) and processed HYCOM data near the Chukchi slope (version 2) ... - Ku, Ahyoung; Park, Jae-Hun (SEANOE, 2024)
Quasi-seasonal and quasi-monthly variations of near-bottom temperature were observed using Current and Pressure-recording Inverted Echo Sounders (CPIES) deployed on the slope between the Canada basin and the Chukchi shelf from August 2018 to July 2020.They were equipped with a 4930R ZPulse Doppler current sensor positioned approximately 51 m above the seafloor, which measured near-bottom current and temperature. Among the variables CPIES measured, we used the near-bottom temperature, the resolution and accuracy of which are 0.01°C and 0.1°C, respectively. We also used temperature, velocity, and sea surface height data from the Hybrid Coordinate Ocean Model (HYCOM). We collected outputs from the HYCOM + NCODA Global 1/12° GOFS 3.1 41-layer analysis (GLBy0.08 Experiment 93.0). It has a horizontal resolution of 0.08° × 0.04° (zonal and meridional, respectively) and a temporal resolution of 3 h. ...